2020
DOI: 10.1016/j.waojou.2020.100484
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of skin diseases in children 1 to 6 years old in the city of Bogota, Colombia

Abstract: Background: Skin diseases represent an important part of the morbidity among children and are possibly influenced by geographic, racial, social, cultural, and economic factors. Despite being so frequent around the world, skin diseases have not been important in developing strategies in public health. Aim: The purpose of this study was to evaluate the prevalence of skin diseases among the student population between 1 and 6 years of age in Bogotá, Colombia between March 2009 and June 2011. Materials and methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
9
0
1
Order By: Relevance
“…All of them were written in English. No study written in German, Spanish or French met the inclusion criteria 14‐57 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All of them were written in English. No study written in German, Spanish or French met the inclusion criteria 14‐57 …”
Section: Resultsmentioning
confidence: 99%
“…More than half of the studies (n = 23) were restricted to children (Figure 2 ). 15,16,17,19,21,24,25,26,28,29,30,32,34,38,39,40,41,49,50,52,54,55,56 As Figure 2 shows, 17 studies were performed in Africa, 14,15,16,19,20,21,22,26,28,29,30,34,36,46,48,49,50,57 12 studies in Oceania, 27,33,35,37,39,42,43,44,45,…”
Section: R E Su Ltsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Many prior studies either showed a low prevalence of PVC or did not include it as a diagnosis, owing to the condition's minor symptoms. 5,20,22 There was a slight difference with Oke et al (2014), who reported tinea capitis as the most frequent infection, with a prevalence of 26.9%, followed by PVC (4.4%) 5 As observed by Kipronoet al (2015) Tinea capitis was also the pediatric skin fungal disease who appeared the most. 23 Haircuts at local barbers, poor personal hygiene, short hair that favors transmission from one scalp to the other, and increasing frequent interaction with playmates at school and younger siblings at home could account for the prevalence of tinea capitis among children.…”
Section: Discussionmentioning
confidence: 89%
“…It is influenced by geography, season and climate, socioeconomic factors, and personal hygiene. [1][2][3] In developed countries, skin infection is still a cause of morbidity. Its incidence is more common than pneumonia and urinary tract infection.…”
Section: Introductionmentioning
confidence: 99%